Fiscal decentralization and its impact on industrial development in Jambi Province - M. Syurya Hidayat; Faradila Herlin (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study aims to analyze: 1) factors influencing the degree of fiscal decentralization in Jambi Province; 2) the influence of the degree of fiscal decentralization on the industrial sector in Jambi Province. The analysis model is the panel data regression. The results showed that, first, the economic level, the amount of regional spending, and the investment level significantly influence the degree of fiscal decentralization in Jambi Province. Second, there is a significant impact of the degree of fiscal decentralization on the development of the industrial sector in Jambi Province. This study recommends increasing local own-source revenue in order to improve the degree of fiscal decentralization. Furthermore, the allocation of regional expenditure must be directed towards direct expenditure, especially capital expenditure, which is related to industrial development in Jambi Province.